2020
DOI: 10.1002/qre.2696
|View full text |Cite
|
Sign up to set email alerts
|

Median control charts for monitoring asymmetric quality characteristics double bounded

Abstract: In many practical situations, the quality characteristics of interest assume values in the range (0,1), like rates and proportions (but they are not results from Bernoulli experiments). Most control charts built for these quality characteristics rely on monitoring parameters of their probability distribution functions or on their averages after some reparameterization of their density probability function. However, for highly asymmetric distributions, the median is a more appropriate location parameter than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…As considered in ref. [42] and due to the expensive computational time consumption of the resampling methods, we just consider the case‐K (where the bootstrap is replaced by Monte Carlo simulations) and the control limits determined by the same distribution considered in the data generation. For a fixed α value, we consider the following algorithm to evaluate the circular control charts with subgroups: …”
Section: Control Chart Performancementioning
confidence: 99%
“…As considered in ref. [42] and due to the expensive computational time consumption of the resampling methods, we just consider the case‐K (where the bootstrap is replaced by Monte Carlo simulations) and the control limits determined by the same distribution considered in the data generation. For a fixed α value, we consider the following algorithm to evaluate the circular control charts with subgroups: …”
Section: Control Chart Performancementioning
confidence: 99%
“…Du Nguyen and Phuc Tran 53 suggested two one‐sided control charts to detect the ratio between two normal random variables that play a significant role in various processes, the outcome showed that the advantages of the one‐sided control chart outweigh the two one‐sided charts in monitoring and perceiving any minute shift in a procedure in a factory or nonmanufacturing environment. Lima‐Filho et al 54 . developed a chart to trace the observations taken from quality features, which double bounded after reparameterization of the probability density functions.…”
Section: Introductionmentioning
confidence: 99%